Influence of SDR Resistance Value on Low Voltage Ride Through Capability of Doubly Fed Induction Generator. Issue 6 (February 2019) - Zhao, Peng; Luan, Fengkui; Bo, Lin; Lyu, Weilong; Jia, Jing; Zhang, Yong; Li, Guanglei; Yu, Peng
Abstract: For the increasing rate of wind generation capacity, the grid codes for grid connected wind turbines evolve continuously and demand that the wind power generator has to ride through the grid faults. In this paper, the new LVRT scheme which based on SDR is presented. Analyzing the new LVRT topological structures of DFIG with SDR circuit topology and the effect of the DBR circuit during grid voltage dip, The mathematical models of the equivalent circuit of DFIG power system during normal voltage and grid voltage dip are established. Through analyzing the mathematical models of DFIG power system during normal voltage and grid voltage dip, the feasibility of the new LVRT scheme is verified. The DFIG power system mode is built with Matlab/Simulink to validate its effectiveness. Simulation results show that DFIG can operate in connection with grid to stabilize the grid voltage during fault and SDR resistance selection could guarantee to limit the rotor current and consider rotor overvoltage.